(untitled) (Sociologisk Forskning, 1995)
The issue of the problems of the natural environment, presently taking a central part of the societal agenda, reveals a situation in which social science in general, and sociology in particular, is confronted with two major questions: the first one concerns how environmental problems are to be conceptualized from a strict social scientific, as distinguished from a natural scientific point of view; the second one has to do with the normative relation of social science to the political problematization of environmental concerns. Taking a communication theoretical point of departure, mainly following the ideas of Niklas Luhmann and Ulrich Beck, it is argued in this article that the environmental problem may be conceptualized in terms of the internal, social, as opposed to the external, natural ecology of the functionally differentiated modem society. As sociologists we are returned to the original intention of the discipline, namely, that social facts can be explained only by social facts. In this context the notion of risk - conceived of as the problem of decision-making in the face of a spatially and temporally contingent and uncertain environment - will be of central importance. The perspective presented here suggests a sociological reconceptualization meant to grasping the idea of a societal system no longer having the achievement of security as its primary goal, but rather the exploitation of uncertainty and contingency itself: scientifically, ethically and politically.